Sebaran Karbohidrat pada Kelenjar Ludah Biawak Air (Varanus salvator) (DISTRIBUTION OF CARBOHYDRATES IN THE SALIVARY GLANDS OF WATER MONITOR (VARANUS SALVATOR)) - Nasution, Idawati; Saputra, Alfajri; ., Hamny; Jalaluddin, Muhammad; Wahyuni, Sri (Jurnal Veteriner, 2015)
The objective of this study was to determine the carbohydrate content of salivary glands lingual,sublingual, and mandibular glands of water monitor (Varanus salvator). This studywas used the lingualglands, sublingual, and mandibularof an adult male water monitor. Salivary glands were fixed by soakingin a solution of 4% paraformaldehyde for four days. Then, the tissuewas processed into routine histologicalpreparations. Salivary gland tissue was stained with alcianblue staining (AB) pH 2.5 for detecting acidiccarbohydrates and was stained with periodic acid Schiff (PAS) for detecting neutral carbohydrates. Theresults showed that the lingual and sublingual glands showed a positive reaction to AB pH 2.5 stainingand PAS with the intensity varied from weak (+) to strong intensity (+++) scattered in the cytoplasm of thecell. In the cytoplasm of cells of the mandibular glands showed negative reaction (-) to the AB pH 2.5staining but reacted positively to PAS with the intensity varied from weak (+) to strong (+++). Based onthe result of the study it can be concluded that lingual and sublingual glands of Water monitor containacidic and neutral carbohydrates while mandibular glands only contain neutral carbohydrates.
Keywords: watermonitor, acidic carbohydrates, neutralcarbohydrates, salivaryglands